Efektivitas Penggunaan Media Audio Visual Terhadap Kecerdasan Spiritual Anak Kelompok B Di TK ABA III Paranga - Astryani Muhamad; M Yusran Rahmat (Jurnal Studi Guru dan Pembelajaran, 2022)
The problem in this study is whether the use of audio-visual media is effective on the spiritual intelligence of group B children in Aisyiyah Bustanul Athfal III Kindergarten, Bajeng District, Gowa Regency with the aim of knowing the effectiveness of using audio-visual media on the spiritual intelligence of group B children in Aisyiyah Bustanul Athfal III Kindergarten Paranga Bajeng District, Gowa Regency. This type of research is an experimental research design using the One Group Pretest-Posttest design which consists of pretest, treatment and posttest. The subjects in this study were 10 children in group B. The results showed that the use of audio-visual media was effective on the spiritual intelligence of group B children in TK Aisyiyah Bustanul Athfal III Paranga which showed that the average pretest score was 7.4 and the posttest average was 16.1 and was also supported by the results of calculations using the Wilcoxon Signed Rank Test on the SPSS program obtained the Asymp value. Sig. (2 tailed) of 0.005, here is a probability of 0.05 or (p < 0.05) which means H0 is rejected and H1 is accepted. Based on the results of this study, it can be concluded that the use of audio-visual media is effective on the spiritual intelligence of group B children at Aisyiyah Kindergarten Bustanul Athfal III Paranga, Bajeng District, Gowa Regency